KLASIFIKASI PENUTUP LAHAN BERBASIS OBJEK PADA DATA FOTO UAV UNTUK MENDUKUNG PENYEDIAAN INFORMASI PENGINDERAAN JAUH SKALA RINCI - Sari, Nurwita Mustika; Kushardono, Dony (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2014)
The need of spatial information from detailed-scale remote sensing is increasing. Unmanned Aerial Vehicle or UAV become one of vehicles that is expected to obtain such information. Production of land cover spatial information using UAV photo data requires appropriate method for classification. This study proposes an object-based classification method for land cover based on Haralick texture information namely homogeneity, contrast, dissimilarity, entropy, angular second moment, mean, standard deviation, and correlation. As a comparison method, a conventional land cover-object-based classification is implemented using the same information features, there are brightness, compactness, and density. The result shows that method using texture feature in object-based classification has reached 95.22% accuracy or 17.5% difference that is much better than conventional method that reaches 77.71%.